Research on Tourist Satisfaction Evaluation of Macau’s Built Heritage Space Under the Genius Loci - Pohsun Wang; Chenxi Li; Jing Liu (Buildings)
As a typical World Cultural Heritage city, Macau has a special regional identity and outstanding cultural value in the built heritage and spatial identity of the city. As contemporary cultural industries have undergone rapid development to transform architectural heritage spaces into displays into showcases of heritage significance, an adaptive transformation strategy is not to be ignored. Although the current transformations demonstrate functional efficacy, they lack of a cultural environment, the Gestalt of the Genius Loci, and a limited visitor experience. For this research, we use the Genius Loci theory to identify constitutive spatial elements and derive theory-based evaluation criteria for the Mandarin’s House, which acts as the case study. It provides a comprehensive evaluation framework across four dimensions: spatial perception, cultural identity, emotional engagement, and functional attributes, each one comprising 20 specific indicators. This research reviews the factors that affect the recognition of cultural identity through quantitative analysis using Importance–Performance Analysis (IPA), evaluating the importance–performance relationships of these indicators. Critical gaps between visitor expectations and current spatial performance are found. Therefore, four optimization strategies are proposed accordingly. (1) Physical experience is enriched through reconstruction of spatial narrative; (2) spiritual experience is reinforced through cultural memory activation; (3) regional characteristics are strengthened through the contextualization of heritage values; and (4) sustainable development mechanisms for adaptive reuse are established. Taken as a systematic approach, it offers both theoretical and practical insight into the regeneration of the architectural heritage spaces in the World Cultural Heritage cities.